Fatigue in men and women who have returned to work after stroke: Assessed with the Fatigue Severity Scale and Mental Fatigue Scale - Anna Norlander; Ingrid Lindgren; Hélène Pessah-Rasmussen; Gunvor Gard; Christina Brogårdh (Medical Journals Sweden, 2021)
Objective: To assess the occurrence of self-reported fatigue among men and women who have returned to work after stroke, and the association between 2 fatigue rating scales. Design: A cross-sectional study. Subjects: A total of 91 adults (58 men/33 women, mean age 53 years) with mild to moderate disability. Methods: Questionnaires were posted to participants approximately one year after stroke. Fatigue was assessed with the Fatigue Severity Scale (FSS) and the Mental Fatigue Scale (MFS). Results: In total, 58% of the women and 33% of the men reported fatigue on the FSS (total score ≥ 4), and 46% of the women and 28% of the men reported mental fatigue on the MFS (total score ≥ 10.5). Being easily fatigued, decreased motivation, mental fatigability and sensitivity to stress were the most reported problems. FSS and MFS were moderately associated (rho 0.517-0.732). Conclusion: Fatigue is common among persons who have returned to work after stroke, and interferes with daily life. The long-term consequences of fatigue should be addressed after stroke, especially in women. The FSS and the MFS can be used in combination, as they provide information on different aspects of fatigue.